RESPONS PERMINTAAN PANGAN TERHADAP PERTAMBAHAN PENDUDUK DI SUMATERA BARAT - Rusda Khairati; Rahmat Syahni (Jurnal Pembangunan Nagari, 2016)
The objective of this research is to estimate the demand response ofmain food (rice, meat, egg, and milk) to population increasein West Sumatera.To achieve this objective, we use multiple regression analysis using secondary data of West Sumatera from 2002 to 2013. In this case we use the product price, total population, and per kapita income asindependent variabels; and food demand as dependent variabel. The result shows that only total population significantly influence the demandon rice, meat, eggs, and milk, with coefficient of response8% for rice; 2.95% for meat; 4.37% for eggs, and14.03% for milk.These numbers shows that the demand on food is very elastic to the increase of total population. It means that the 1% increase on total population, would increase about 8% demand on rice; about 2.95% demand on meat; 4.37% demand on eggs, and 14.03% demand on milk.